Experimental and Analytical Study on Deformation Behavior in Hogging Moment Regions of Composite Beams. (30th December 2020) - Song, Aiming; Luo, Qi; Wan, Shui; Li, Zhicong
Abstract : The results of an experimental and analytical study on the static and fatigue behavior in steel-concrete composite beams under the hogging moment were presented in this paper, and the structural deformation was discussed cautiously and emphatically. Firstly, the static and fatigue tests on three inverted simply supported beams were conducted. The development of cracks under static loading, the load-deformation curves, and the values of residual deformation under fatigue load were recorded and analyzed in detail. Several meaningful conclusions were obtained from the analysis of experimental results. To study the development laws of residual deformation under fatigue load, the analytical methods of residual midspan deflection and residual rebar strain were proposed, respectively. The limitation and accuracy of the presented models were studied according to the comparison between the prediction and measured results. The calculation values of the proposed models showed good agreement with the test results. Finally, the design recommendations of fatigue deformation were proposed according to the experimental and analytical study on steel-concrete composite beams subjected to hogging moment.